Inclusione e didattica della plusdotazione: le rappresentazioni degli educatori e degli insegnanti in formazione iniziale e in servizio - Barbara De Angelis (LED Edizioni Universitarie, 2017)
Inclusion and didactics of giftedness: educators, school teachers and preservice teachers' perceptions. The exploratory study searches to evaluate the question on how knowledge about gifted education - as a topic still underrepresented in the legislation and educational research in Italy - is spread within a population of either school teachers and students studying to become school teachers. Therefore, this work marks an important step towards the goal of improving the knowledge of teaching methods, and emphasizes strategies of inclusion by exploring different approaches in order to facilitate the recognition of the special educational needs of gifted children. In this research participated 70 third and fourth semester university students following the courses SDE (Scienze dell'Educazione), EPC (Educatore Professionale di Comunità) and SFP (Scienze della Formazione Primaria) during the academic year 2016/17, and 35 teachers of primary and secondary schools. The results indicate that gifted education has been widely excluded from special and inclusive education practices, and bring into focus the need to reflect critically on service and preservice teaching preparation. In order to eventually increase the quality of education, and to outline the operating practices towards gifted education, it seems inevitable to deepen this approach with further qualitative and quantitative research. Therefore, the present study confirms the key role of the inclusive teacher towards fulfilling the special educational needs of a student with high cognitive potential.